The Instagram as a tool for scientific dissemination in astronomy: a case study in Ceará’s Cariri region - Souza, Claudio do Nascimento; Duarte, Tharcísyo Sá e Sousa; Junior, Gilson Francisco de Oliveira; Costa, Jefferson Soares da; Martins, Milene Rodrigues (Cadernos de Astronomia, 2024)
This study explores the potential of Instagram as a tool for science communication in Astronomy, detailing the experiences of an extension project at the Universidade Federal do Cariri, specifically during the COVID-19 pandemic. By analyzing data from a page linked to the project, we observed the potential of the network and the predominance of a young audience engaged with such content. In addition, we analyzed data from the Olimpíada Brasileira de Astronomia e Astronáutica, during the period from 2012 to 2020, and observed a significant drop in participation from schools in Cariri Cearense, possibly due to a lack of incentive in the area and the COVID-19 pandemic. The project’s active methodology, combined with the use of tools such as Stellarium and the creation of cultural materials such as cordéis and scientific comic strips, proved to be effective in spreading astronomical knowledge. It is therefore concluded that this social network, with its combination of attractive images, concise information, interactive resources and a wide reach, is a promising tool for scientific dissemination in astronomy and other areas of knowledge in our region.